Concreting works / Nur Atiqah Najihah Zakaria - Zakaria, Nur Atiqah Najihah (Universiti Teknologi MARA, Perak, 2018)
First and foremost, this practical training report is about the construction and concreting works of Jabatan Kerja Raya Kemaman (JKR Kemaman) which is to construct Klinik Kesihatan (Type 7). This construction is located at Seberang Tayor, Kemaman, Terengganu. Jabatan Kerja Raya Kemaman (JKR Kemaman) has appointed Jurubena Pakatan Setia Sdn. Bhd as the main contractor to work up on the project called Klinik Kesihatan (Type 7). For your information, this internship report has been divided into several chapter which are contains five (5) chapters. In chapter 1, it contains the introduction of internship company which is JKR Kemaman. It will discuss more about history of company such as the age of the building, locations of the company, vision and mission of company and also the adjacent building. Next, in the chapter 2 is about literature review which is means it will discuss more deeply about the industry of the construction and concreting works and some research through the website and some books that have been provided in JKR Kemaman. From the book given, it shows the definitions of concrete, types of concrete and types of materials that have been used in order to produce a good mixture of concrete such as cement, aggregates, water and admixtures. For the chapter 3, it will be the start of case study. It provides the details of the construction such as the title of construction, building elevation and others, so it will be easier to understand the process of concreting works. Then, it also will explain about the concreting test that must been done before concreting works. There are two types of concreting test that must been done such as slump test and cube test. Finally, in the chapter four (4) and five (5), I have prepared a list of problems that have been occurred during the construction and also provides the recommendations in order to improve the quality of the construction.